Pengaruh Pelatihan Dan Budaya Organisasional Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening (Survey Pada Departemen Sumber Daya Manusia Di Pt. Madubaru Pg/Ps Madukismo) - Dihan, Fereshti Nurdiana; Pratama, M. Rizky (Jurnal Bisnis : Teori dan Implementasi, 2018)
This study discusses the effect of training and organizational culture on performance with job satisfaction as intervening variable. Respondents in this study were 73 employees in the human resources department at PT. MADUBARU PG / PS MADUKISMO. The purpose of this study is to determine the effect of training on employee performance partially, the influence of organizational culture on employee performance partially, the effect of training on job satisfaction partially, the influence of organizational culture on job satisfaction partially, the influence of job satisfaction on employee performance partially, to find out whether job satisfaction mediates the effect of training on employee performance, to find out whether job satisfaction mediates the influence of organizational culture on employee performance. The results of this study show that partially there is a positive and significant influence between training on employee performance, partially there is a positive and significant influence between organizational culture on employee performance, partially there is a positive and significant influence between training and job satisfaction, partially there is a positive influence and significant between organizational culture to job satisfaction, partially there is a positive and significant influence between job satisfaction on employee performance. In this study also proved that job satisfaction mediate the effect of training on employee performance, job satisfaction mediate the influence of organizational culture on employee performance in the department of human resources PT. MADUBARU PG / PS MADUKISMO.